Developing A Multi Discriminant Analysis Model As A Tool To Predict Insolvency Of Property Development Firms In Malaysia - Ismail, Maziah; Fredy, Andereas Goentoro (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1997)
Since the last three decades, statistical techniques such as Multiple Discriminant Analysis (MDA) have been used by researchers to predict corporate failures (Altman: 1992). However, to date these techniques have not been tested on property related financial racios comcerning loans undertaken by property development firms.